Public Policy Implementation: A Theoretical Review - Kurhayadi Kurhayadi (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2023)
The purpose of this investigation is to contextualize the theoretical discussions that have been had by various authors regarding the concepts and models of public policy and their respective execution, with the intention of provoking questions and thought. It is the focus or role of public policy as a mechanism for solving societal problems. Public power seeks to anticipate the need for planning and implementing actions that can create structural conditions for socioeconomic development. This work takes the form of a bibliographic study, and it regards the focus or role of public policy as a mechanism for solving societal problems. Discussion focussed on competing for top-down and bottom-up perspectives regarding the various implementation options investigated. In addition, he cites a significant body of explanatory variables that help improve one's comprehension of implementation. One example of this is the 5-C protocol, a conceptual framework that, in the opinion of several academics, is becoming increasingly recognized as an important factor in the chain of causation. The relevance of implementation in the planning process was acknowledged by the literature later than it should have been due to the typical view scholars have of political science, which is to concentrate on examining legislative or executive administrative procedures. Because of the numerous unsatisfactory outcomes, it is clear that the implementation and the elaboration stages needed to be coordinated.